2008
DOI: 10.1088/0022-3727/41/22/223001
|View full text |Cite
|
Sign up to set email alerts
|

Solid polymer electrolytes: materials designing and all-solid-state battery applications: an overview

Abstract: Polymer electrolytes are promising materials for electrochemical device applications, namely, high energy density rechargeable batteries, fuel cells, supercapacitors, electrochromic displays, etc. The area of polymer electrolytes has gone through various developmental stages, i.e. from dry solid polymer electrolyte (SPE) systems to plasticized, gels, rubbery to micro/nano-composite polymer electrolytes. The polymer gel electrolytes, incorporating organic solvents, exhibit room temperature conductivity as high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
626
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 914 publications
(638 citation statements)
references
References 164 publications
9
626
0
3
Order By: Relevance
“…Crystallization of PEO is known to markedly decrease the ionic conductivity of ICMs made by traditional casting or blending 11,31 . However, in the (PEO/ANF) n composite we do not observe crystalline phase even though the polymer is deposited at room temperature, with and without lithium triflate, before and after soaking in electrolyte.…”
Section: Barementioning
confidence: 99%
“…Crystallization of PEO is known to markedly decrease the ionic conductivity of ICMs made by traditional casting or blending 11,31 . However, in the (PEO/ANF) n composite we do not observe crystalline phase even though the polymer is deposited at room temperature, with and without lithium triflate, before and after soaking in electrolyte.…”
Section: Barementioning
confidence: 99%
“…This is expected to double the energy density and eliminate the volatile organic solvents, which pose a fire hazard. 4,6 For a solid material to replace liquid and gel electrolytes, it should have a minimum ion conductivity of 10 −3 S cm −1 throughout the expected range of operating temperatures.…”
mentioning
confidence: 99%
“…One method is to inhibit heat generation by adopting alternative electrolytes, e.g., polymer gel electrolytes and solid-state electrolytes with low ionic conductivities. [71][72][73][74] The other route is to release or absorb the heat before overheating, e.g., employing safety vents, extinguishing agents, or a thermal fuse. [70,[75][76][77][78] Although these related studies showed some effects in thermal protection, they are limited by the passive strategies with significant sacrifices of energy storage performance and irreversible self-protection reactions.…”
Section: Smart Design To Avoid Overheatingmentioning
confidence: 99%